World commerce and governments : trends and outlook - Woytinsky, Wladimir S.; Woytinsky, Emma Shadkhan (New York : Twentieth Century Fund, 1955)
The purpose of the volume is to study world trends during the fateful era in which the mechanized economy originated on the two coasts of the North Atlantic. The volume deals with the exchange of goods among peoples; transportation within national communities and in the world as a whole; governments and their interrelationships - supranational organizations and international cooperation.
Includes index
"Source references": p. [863]-888.
rpm 22/01/2019
Loans
Keywords: Commerce; Transportation; Political science